2022
DOI: 10.1190/int-2021-0173.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the sensitivity of seismic facies classification to seismic attribute selection: An explainable machine-learning study

Abstract: During the past two decades, geoscientists have used machine learning to produce a more quantitative reservoir characterization and to discover hidden patterns in their data. However, as the complexity of these models increase, the sensitivity of their results to the choice of the input data becomes more challenging. Measuring how the model uses the input data to perform either a classification or regression task provides an understanding of the data-to-geology relationships which indicates how confident we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For the regression problem, the average of all the regression decision tree output values is used as the prediction of the forest. Previous work in geophysics has shown that for RF classification, such as lithology and fluid identification, using several target-sensitive elastic properties obtained by pre-stack seismic inversion as input feature variables can yield good classification results (Kim et al, 2018;Lubo-Robles et al, 2022). However, for the regression of continuous numerical variable such as TOC, the influence of the number of elastic properties on the prediction results is not clear enough.…”
Section: Feature Variables Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the regression problem, the average of all the regression decision tree output values is used as the prediction of the forest. Previous work in geophysics has shown that for RF classification, such as lithology and fluid identification, using several target-sensitive elastic properties obtained by pre-stack seismic inversion as input feature variables can yield good classification results (Kim et al, 2018;Lubo-Robles et al, 2022). However, for the regression of continuous numerical variable such as TOC, the influence of the number of elastic properties on the prediction results is not clear enough.…”
Section: Feature Variables Extensionmentioning
confidence: 99%
“…(2019) developed a robust support vector machine (SVM) learning approach to identify high TOC formations. Among different supervised learning strategies, the Random Forests (RF) has been increasingly applied in the field of geophysics (Cracknell and Reading, 2014;Kim et al, 2018;Lubo-Robles et al, 2022). The RF is an ensemble learning algorithm, which combines the idea of bagging ensemble and random feature selection, and the prediction result is determined by voting with multiple weak classifiers (Breiman, 2001).…”
Section: Introductionmentioning
confidence: 99%